2018
DOI: 10.1002/2017gc007122
|View full text |Cite
|
Sign up to set email alerts
|

Paleoaltimetry Potentiality of Branched GDGTs From Southern Tibet

Abstract: Paleoaltimetric reconstructions of the southern Tibetan Plateau (TP) are crucial to understand the processes and mechanisms concomitant with the tectonic collision of the Indian and Eurasian continental plates. We measured the branched glycerol dialkyl glycerol tetraether (brGDGT) indices from 88 surface soils from the southern TP and found that alkaline soils exhibited lower MBT′ and MBT′/CBT‐derived MAT (mean annual temperature), while MBT′/CBT‐derived MAT exhibited a strong correlation with altitude (R2 = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 56 publications
(170 reference statements)
1
13
0
Order By: Relevance
“…This suggests that the global calibration for temperature reconstruction with brGDGT distributions from De Jonge, Hopmans, et al (2014) is applicable in the Himalaya. Several studies have shown that brGDGT‐based indices are correlated with adiabatic temperature change along elevation profiles in different regions worldwide (e.g., Bai et al, 2018; Deng et al, 2016; Ernst et al, 2013; Peterse et al, 2009). This agrees with the calculated MAT GDGT of Himalayan soils which strongly correlates with elevation (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the global calibration for temperature reconstruction with brGDGT distributions from De Jonge, Hopmans, et al (2014) is applicable in the Himalaya. Several studies have shown that brGDGT‐based indices are correlated with adiabatic temperature change along elevation profiles in different regions worldwide (e.g., Bai et al, 2018; Deng et al, 2016; Ernst et al, 2013; Peterse et al, 2009). This agrees with the calculated MAT GDGT of Himalayan soils which strongly correlates with elevation (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…With the assumption that contrasting tetraether temperatures of paleosol and lacustrine facies are related to sources (i.e., the in situ production in the basin vs. the terrestrial inputs), we can estimate the difference in elevation between the basin and the surrounding mountain ranges. The compiled global data shows that the tetraether‐derived temperature lapse rates range from 4.8 to 7.9 °C per 1,000 m (Bai et al, ). The lacustrine temperatures show overlapping with the paleosols as well as difference reaching 10 °C, which suggests the temporal and/or spatial variations in tetraether fluxes into the paleolake.…”
Section: Estimating the Paleo‐reliefmentioning
confidence: 99%
“…Due to the underestimation of MBT′/CBT‐derived mean annual air temperatures in an alkaline environment (Bai et al, ; H. Wang et al, ), the MBT′/CBT index may be less accurate. Here we restrict the discussion to an evaluation of proxy MAT mr values (Figure c).…”
Section: Paleoenvironmental Data Based On Gdgtsmentioning
confidence: 99%
“…Microbial‐branched glycerol dialkyl glycerol tetraether (brGDGT) paleotemperature proxies, in the form of the MBT (MBT′)/CBT ratios, have been developed (Weijers et al, ) over the past decade and have been widely used to reconstruct terrestrial paleotemperatures (e.g., Donders et al, ; Weijers et al, ) and paleoaltitudes (Anderson et al, ; DeCelles et al, ; Deng & Jia, ; Hren et al, ; Zhuang et al, ). However, these proxies are affected greatly by alkalinity and aridity (Bai et al, ; Dirghangi et al, ; H. Wang et al, ; H. Yang et al, ). New brGDGT paleotemperature proxies, that is, the MAT mr and MBT′ 5ME proxies, were therefore defined after removing the 6‐methyl isomers; these latter proxies are thus less affected by alkalinity (De Jonge et al, ; Naafs et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation